2017
DOI: 10.1242/jcs.201335
|View full text |Cite
|
Sign up to set email alerts
|

Rewiring of embryonic glucose metabolism via suppression of PFK-1 and aldolase during mouse chorioallantoic branching

Abstract: Adapting the energy metabolism state to changing bioenergetic demands is essential for mammalian development accompanying massive cell proliferation and cell differentiation. However, it remains unclear how developing embryos meet the changing bioenergetic demands during the chorioallantoic branching (CB) stage, when the maternal-fetal exchange of gases and nutrients is promoted. In this study, using metabolome analysis with mass-labeled glucose, we found that developing embryos redirected glucose carbon flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 44 publications
3
29
0
Order By: Relevance
“…Despite these limitations, enzyme histochemistry represents a large toolbox with diverse possibilities of application, which allows us to assess the adaptations of various enzymatic activities, including transferases (for instance kinases), hydrolases, and lyases (van Noorden and Frederiks, 1992). We see emerging MALDI imaging techniques as powerful complementary tools to quantify small molecules in situ in order to additionally provide spatial information on substrate bioavailability (Fujimura and Miura, 2014;Miyazawa et al, 2017;Schwamborn et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Despite these limitations, enzyme histochemistry represents a large toolbox with diverse possibilities of application, which allows us to assess the adaptations of various enzymatic activities, including transferases (for instance kinases), hydrolases, and lyases (van Noorden and Frederiks, 1992). We see emerging MALDI imaging techniques as powerful complementary tools to quantify small molecules in situ in order to additionally provide spatial information on substrate bioavailability (Fujimura and Miura, 2014;Miyazawa et al, 2017;Schwamborn et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with previous findings in epithelial cells, 144 fibroblasts, 295,296 and developing embryos 297 which show that glycolysis regulates glucose entry into the PPP. Our findings are also consistent with computational predictions of the role of PFK in regulating the PPP in the intact heart.…”
Section: Discussionsupporting
confidence: 94%
“…In particular, developing embryos increase PPP flux by decreasing PFK enzyme abundance, rewiring glucose metabolism for normal development. 297 In the context of the adult heart, pathological hypertrophy [132][133][134] and heart failure 135 are both associated with an increase in PPP activity. During short-intensive exercise, the activities of the enzymes of the oxidative part of the PPP have been found to be slightly diminished; however, in the immediate recovery period, an increase in enzymatic activity was observed that persisted for up to 3 h. 306 While the effectors of increased PPP activity are not well known, a recent study identified that overexpression of PGC-1α in skeletal muscle increased the enzymatic activities and end-products of the PPP.…”
Section: Metabolic Regulation Of Cardiac Growthmentioning
confidence: 99%
“…Metabolic changes play essential roles during embryogenesis and tumorigenesis (22,23). For example, aerobic glycolysis facilitates biomass production during embryo development (24).…”
Section: Introductionmentioning
confidence: 99%